Implementation of Developing Business Strategy in the Era of Digital Transformation - Kusuma Hadi, Muhammad Wahyu; Amin, Fathul; Khairunnisah, Noni Antika; Damayanti, Sri (Business Management, 2025)
An effective strategy is essential for any business as modern businesses undergo digital transformation. When you create a digital business strategy, there are many important things to consider. The most important thing is to increase the scope of business operations and use the latest IT solutions. As such, this strategy will be considered a. long-term “improvement” plan aimed at maintaining performance, viability and contribution to achieving the Sustainable Development Goals (SDGs). The purpose of this article is to see how to create an effective business strategy in the digital era. This analysis uses a qualitative descriptive approach. The results of the discussion show that, in the age of the “new economy” and the digital transformation that accompanies it, an innovative digital business strategy that relies on advanced IT solutions and is aligned with the SDGs is a great opportunity for companies to break out from competitors and gain a competitive advantage